2018
DOI: 10.1002/sce.21476
|View full text |Cite
|
Sign up to set email alerts
|

Engaging students in computational modeling: The role of an external audience in shaping conceptual learning, model quality, and classroom discourse

Abstract: Research suggests that designing for an external audience may support conceptual understanding by offering students increased opportunities to reframe perspectival thinking in ways that support domain‐specific reasoning. While this argument is theoretically compelling, to our knowledge, it has not been empirically tested in terms of comparing the conceptual growth of students designing computational models for an external audience to the conceptual growth of students designing computational models for a classr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…On the other hand, in recent years the use of software has become ubiquitous in education settings [16][17][18][19][20][21]. It is well known that laboratory equipments are of significant importance in chemistry lab.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in recent years the use of software has become ubiquitous in education settings [16][17][18][19][20][21]. It is well known that laboratory equipments are of significant importance in chemistry lab.…”
Section: Resultsmentioning
confidence: 99%
“…[9]. In addition, these tools contribute to the development of critical thinking and reflection on the part of the student youth, since students become involved in modelling the studied object and can observe and evaluate the results of their actions [10]. Meanwhile, we stress the need to find new cognitive paradigms covering the classifications of knowledge, concepts, essence of scientific categories related to processes occurring in the learning environment, especially in the open, computer-oriented one.…”
Section: State Of Artmentioning
confidence: 99%
“…ESSs were shown to effectively support iterative and social learning, enabling learners produced, shared, and reviewed each other's computational artifacts. Pierson and Clark () investigated the role of external audience in engaging students in computational modeling. This study found that students who designed for an external audience of younger children displayed greater conceptual growth about mechanisms that cause tidal bulges.…”
Section: Seven Emergent Technologies Used In Science Educationmentioning
confidence: 99%
“…Several studies also identified forms of scaffolding that effectively supported learning through agent‐based computational modeling (Brady et al, ; Dickes & Sengupta, ; Pierson & Clark, ; Schwarz et al, ), online mentoring from scientists (Scogin & Stuessy, ), and app‐based procedural guidance (Falloon, ). For instance, modeling environments like StarLogo Nova (Pierson & Clark, ) and Netlogo (Dickes & Sengupta, ) were shown to reduce the syntactic tension experienced by students by allowing them to program through graphical “blocks” rather than text‐based commands. Pallant and Lee () described how students needed explicit scaffolding to recognize and properly respond to model limitations and uncertainty.…”
Section: Seven Emergent Technologies Used In Science Educationmentioning
confidence: 99%